The Easter surprise - McDonnell, Janet, 1962-; Hohag, Linda (Chicago : Childrens Press, 1993)
Julie celebrates Easter by receiving a basket of candy, going to church, and enjoying an Easter egg hunt. Includes instructions for Easter crafts and games.
2.9
K-3
Keywords: Easter -- Fiction; Easter -- Fiction